Answer :

we have,

f (x) = 2*x*^{3}-3*x*^{2}+*ax+b*

Put,

x = 0

f (0) = 2 (0)^{3} – 3 (0)^{2} + a (0) + b

= 0 – 0 + 0 + b

= b

x = -1

f (-1) = 2 (-1)^{3} – 3 (-1)^{2} + a (-1) + b

= -2 – 3 – a + b

= -5 – a + b

Since, x = 0 and x = -1 are roots of f (x)

f (0) = 0 and f (-1) = 0

b = 0 and -5 – a + b = 0

= a – b = -5

= a – 0 = -5

= a = -5

Therefore, a = -5 and b = 0

Rate this question :

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

Zero of the polynRS Aggarwal & V Aggarwal - Mathematics

If 2 and -1/3 areRS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a fRS Aggarwal & V Aggarwal - Mathematics

If (x^{2}RS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

If p(x) = x^{3}RS Aggarwal & V Aggarwal - Mathematics

If p(x) = (x^{}RS Aggarwal & V Aggarwal - Mathematics

The coefficient oRS Aggarwal & V Aggarwal - Mathematics